2019
DOI: 10.4154/gc.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, mineralogical and structural features of native and expanded perlite from Macedonia

Abstract: The physico-mechanical, chemical and mineralogical characteristics of volcanic glass (perlite) from the Mariovo region (Macedonia) as well as the mineralogical changes that occur during its thermal treatment were investigated to demonstrate its utilization for industrial use. The native perlite was characterized by chemical analysis, X-ray powder diffraction (XRPD), infrared (IR) spectroscopy, thermal analysis (TGA/DTA), scanning electron microscopy (SEM-EDX), transmission electron microscopy (TEM), and solid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 13 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…1.6%). Compared to Macedonian perlite [ 48 ], which is considered rich in K 2 O and Na 2 O oxides (4.21% and 3.56%, respectively), Slovak and Hungarian perlite in particular has an even higher K 2 O content, even above 8%, in the case of the medium fraction (SP2) and above 7%—the smallest fraction (SP1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1.6%). Compared to Macedonian perlite [ 48 ], which is considered rich in K 2 O and Na 2 O oxides (4.21% and 3.56%, respectively), Slovak and Hungarian perlite in particular has an even higher K 2 O content, even above 8%, in the case of the medium fraction (SP2) and above 7%—the smallest fraction (SP1).…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the publication [ 19 ] showed that Greek perlite consists mainly of silicate glass (amorphous) and additives in the form of biotite, quartz, and feldspar. In the case of Macedonian perlite [ 48 ], XRD analysis showed the presence of a large amount of aluminosilicate amorphous and small amounts of crystalline, represented mainly by feldspar, quartz, and cristobalite. Feldspar is represented as K-plagioclase, Na-feldspar, and microcline.…”
Section: Resultsmentioning
confidence: 99%
“…Perlite is an amorphous volcanic glass that has relatively high water content, typically formed by hydration of obsidian. 15 Moreover, perlite is able to expand to 4–20 times its original volume (EP, Expanded Perlite) upon heating, resulting in flakes with porosity greater than 95%. 16 Perlite is mainly composed of SiO 2 , Al 2 O 3 , K 2 O, Na 2 O, and combined water, although it may also contain TiO 2 , CaO, MgO, and Fe 2 O 3 at minor quantities depending on its origin.…”
Section: Introductionmentioning
confidence: 99%
“…Republic of Macedonia is rich in inorganic materials with a wide spectrum of potential use and application [1][2][3][4]. Clayey diatomite, found in the vicinity of the Bitola power plant, takes a special place amongst non-metallic materials because it represents a mixture of diatomite and clay minerals [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%